The Effect Of Pregnancy Exercises On The Physical And Psychological Readiness Of Mothers Approaching Labor - Agnes Batmomolin; Rezqiqah Aulia Rahmat; Adisty Dwi Treasa (International Journal of Health Sciences, 2025)
This study aims to determine the effect of prenatal exercise on the physical and psychological readiness of mothers before childbirth. Prenatal exercise is a form of physical activity specifically designed for pregnant women, which is believed to improve physical fitness, reduce stress, and psychologically prepare mothers for childbirth. This study used a quasi-experimental method with a pretest-posttest design on 40 pregnant women in their third trimester who participated in the prenatal exercise program at Community Health Center X. The results showed a significant increase in the physical and psychological readiness of pregnant women after participating in prenatal exercise regularly for 4 weeks. This indicates that prenatal exercise is effective in increasing maternal readiness for childbirth.